Normally-Off AlGaN/GaN HEMTs With a Low Reverse Conduction Turn-On Voltage - Dai-Jie Lin; Chih-Kang Chang; Kuntal Barman; Yu-Chuan Chu; William Shih; Jian-Jang Huang (IEEE Access)
Third quadrant operation is vital for power applications such as synchronous DC-DC converters and inverters, which require a low drain-source voltage drop to reduce conduction losses. However, typical gallium nitride (GaN) transistors have a higher voltage drop when the gate is off. To address this issue, we propose a dual-gate high-electron-mobility transistor (HEMT) to enhance reverse conduction. The device is modulated by the main gate electrode adjacent to the source, while a fixed bias is applied on the auxiliary gate electrode near the drain contact. We achieve a reverse conduction voltage as low as −0.16 V and 89.03 % lower reverse conduction power loss with the proposed device structure. The results can be explained by a freewheeling path between the drain electrode and the auxiliary gate, which enables effective dissipation of the stored charges.